The specificity of cluster training effects in sports: a systematic review and meta-analysis - Zhao, Xinyi; Ya, Xudong; Zhou, Hao; Liu, Guowei; Liu, Ziyao; Luo, Jiaxin; Liu, Yujia; Bu, Yifeng (Frontiers in Physiology, 2026)
ObjectiveTo systematically evaluate cluster structure training (CS) and traditional training (TS) in enhancing athletes’ motor abilities and explore sport-specific effects.MethodsSystematic searches of PubMed, Embase, Cochrane, and Web of Science (inception to March 2025). Quality was assessed using TESTEX, with meta-analyses calculating SMD (P < 0.05) and subgroup analyses by sport.ResultsA total of 11 studies were included, showing that CS outperformed TS in improving athletes’ sprint ability (SMD = −0.32, 95% CI: [−0.56, −0.07], P = 0.012), explosive power (SMD = 0.39, 95% CI: [0.10, 0.68], P = 0.009) with significant differences. Subgroup analysis further revealed sport-specific effects: CS was more effective than TS in enhancing maximum strength (SMD = 0.30, 95% CI: [0.01, 0.59], P = 0.043), explosive power (SMD = 0.96, 95% CI: [0.26, 1.65], P = 0.007), and sprint ability (SMD = −0.65, 95% CI: [−1.15, −0.16], P = 0.009) in volleyball athletes, as well as peak power in soccer athletes (SMD = 0.68, 95% CI: [0.01, 1.36], P = 0.047).ConclusionCS benefits volleyball and soccer, where explosive power is key. Coaches should tailor CS to sports’ energy demands and work-rest ratios.Clinical Trial Registrationhttps://www.crd.york.ac.uk/PROSPERO/home, identifier CRD420251015968.